Improving the Performance of the Satresnarkoba at Klaten District Police to Enhance Drug Crime Eradication and Achieve Law Enforcement to Realize Polri Presisi - Girinata, Nazzer Adhira (Advances in Police Science Research Journal, 2024)
This study is conducted to optimize the performance of the Satresnarkoba in the Klaten District Police and is aimed at increasing the eradication of drug crimes in order to achieve POLRI PRESISI. This study aims to describe the implementation of efforts to combat drug crimes carried out by the narcotics investigation team in the Klaten District Police, as well as the efforts that have been made to optimize the investigation and prosecution in order to eradicate drug crimes in the Klaten District Police jurisdiction. In this final project, the researcher used POAC theory, SWOT analysis, and management theory as analysis tools for the data obtained, accompanied by the use of several concepts and definitions. Data collection was carried out using field research methods, including observation techniques, interviews with sources, and document review. Based on the research conducted, it was found that the efforts to combat drug crimes carried out by the narcotics investigation team in the Klaten District Police have not yet achieved the desired impact due to the increasing number of cases each year, as well as shortcomings in planning, organizing, implementing, and supervising activities that resulted in less than optimal, efforts to eradicate drug crimes as a whole. It can be concluded that the application and optimization of the role of the Satresnarkoba in efforts to combat drug crimes in the Klaten District Police jurisdiction, both in investigation and prosecution, is still not optimal based on the theories used by the researcher in the analysis, as well as internal and external factors that affect the performance of investigators in eradicating drug crimes in the Klaten district.